2017
DOI: 10.1097/md.0000000000008252
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of late-course concurrent versus sequential chemoradiotherapy after mastectomy and axillary surgery in locally advanced breast cancer

Abstract: Background:Concurrent chemoradiotherapy could increase the local control rate in patients with high recurrence risk after breast-conserving surgery, but the effect of concurrent chemoradiotherapy after mastectomy and axillary dissection is not clear. The aim of the study was to compare the effects of late-course concurrent chemoradiotherapy (CCRT) versus sequential therapy (SCRT) after mastectomy and axillary surgery in locally advanced breast cancer.Methods:This was a randomized controlled trial of 155 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Examination of TNM stage in consecutive group therapy showed that 30 patient in the third stage and 22 patient in the simultaneous group therapy are in this stage and considering that most patients are in these stages, which is consistent with the results of other studies in which most patients are in these stages (15). This lack of difference in TNM stage is also consistent with the study of Lu, Y et al (2017) who were not significantly different in TNM stage (16).…”
Section: Discussionsupporting
confidence: 90%
“…Examination of TNM stage in consecutive group therapy showed that 30 patient in the third stage and 22 patient in the simultaneous group therapy are in this stage and considering that most patients are in these stages, which is consistent with the results of other studies in which most patients are in these stages (15). This lack of difference in TNM stage is also consistent with the study of Lu, Y et al (2017) who were not significantly different in TNM stage (16).…”
Section: Discussionsupporting
confidence: 90%
“…The occurrence of grade 1-2 radiation skin reactions was similar in the weekly and 3-weekly paclitaxel groups (89.7% and 88.3%, p = 0.803). It also showed cardio-pulmonary safety [18,19]. Cardiac troponin T is a well-established biomarker of cardiac damage in myocardial infarction due to ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in OS in node positive and negative cohorts. In a recent small randomised trial by Lu et al [ 19 ] the 3-year DFS and OS were reported to be 76.9% and 64.9% for node positive, and 87.2% and 81.8% for node negative cohorts respectively, but without significant difference. They treated all patients with IMRT and reported no grade 3–4 radiation toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation